Changes in energy during treatment of depression: an analysis of duloxetine in double-blind placebo-controlled trials - Harada, E (Int J Clin Pract, 2015)
AIMS: The aim of this study was to assess how quickly and effectively duloxetine improves energy compared with placebo in patients with major depressive disorder (MDD). METHODS: Data from 10 randomised, double-blind, placebo-controlled clinical trials examining duloxetine (40–60 mg/day) vs. placebo in patients diagnosed with MDD were analysed. Change from baseline at Week 1 through Week 8 in Hamilton Depression Rating Scale (HAM-D) retardation subscale score (Item 1 – depressed mood, Item 7 – work and activities, Item 8 – retardation and Item 14 – genital symptoms) was assessed with mixed model repeated measures analysis. Positive predictive values and negative predictive values were calculated for predictor analysis. RESULTS: Patients treated with duloxetine (N = 1522) experienced statistically significantly (p ≤ 0.05) greater reductions in HAM-D retardation subscale scores vs. placebo (N = 1180) starting at Week 1 throughout Week 8 of treatment. Of the patients with early energy improvement (≥ 20% reduction in HAM-D retardation subscale scores) at Week 1, 48% achieved remission (HAM-D total score ≤ 7) at Week 8; 48% and 46% of patients who experienced early energy improvement at Weeks 2 and 4, respectively, achieved remission at Week 8. DISCUSSION: We demonstrated that treatment with duloxetine, quickly and with increasing magnitude over treatment time, improves low energy symptoms. As early as 1 week after starting treatment with duloxetine, improvement of low energy may serve as a predictor of remission at end-point. CONCLUSIONS: Treatment with duloxetine improves energy in patients with MDD and early response in retardation may serve as a modest predictor of remission at end-point. CLINICAL TRIALS REGISTRATION: ClinicalTrials.gov. Study Identifiers: NCT00036335; NCT00073411; NCT00406848 and NCT00536471. Studies HMAQa, HMAQb, HMATa, HMATb, HMBHa and HMBHb predate the registration requirement. DATA POSTING: ClinicalTrials.gov. Study Identifiers: NCT00406848; NCT00536471.